KEANEKARAGAMAN SERANGGA PADA LAHAN PERTANIAN PADI SAWAH DI KAMPUNG BUNGARAYA KABUPATEN SIAK SEBAGAI RANCANGAN BUKU SAKU BIOLOGI SMA KELAS X - Putri Rianti. HS; Suwondo Suwondo; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was conducted to determine the diversity of insects in lowland rice farming in Bungaraya Village, Siak Regency as a biology pocket book design for class X SMA. The study was carried out in lowland rice farming in Bungaraya Village for insect sampling. Meanwhile, insect identification was carried out at the Laboratory of the Biology Education Study Program, Department of Mathematics and Natural Sciences, FKIP, Riau University. This research was conducted in October - November 2021. This research consisted of two stages, namely identification and analysis of insect diversity, the second stage was the design of a pocket book. Parameters measured in this study were insect species composition, insect diversity index, air temperature, humidity, and light intensity. The results showed that the diversity of insects at rice planting age had different diversity. Insect diversity at stations I, II, and III was moderate. The diversity index value at 30 days of rice planting age was 1.87, 60 days of rice planting age was 1.58, and 90 days of rice planting age was 1.55. The types of insects found in lowland rice Oryza sativa Kampung Bungaraya consisted of 5 orders, namely Odonata, Orthoptera, Coleoptera, Hemiptera, and Lepidoptera. The results of the study can be used as an alternative source of learning in the form of a pocket book for learning biology in high school.Key Words: Insect, Arthropoda, Pocket Book, Bungaraya